Planckeon Origin of Dark Energy and Singular Nature of Inflation in Semiclosed Friedman Universe (Global Journal of Science Frontier Research, 2016)
Origins of dark energy and inflation in semiclosed Friedman model universe are sought by examining the imaginary pair of gravitationary bound Planckeon-Higgs boson composite requiring temperature T~10 15 K for thermal creation. Inflation is likely to be related to the singular nature of the transition amplitude D(s 2 ) of the Higgs boson obeying PC-and T-symmetric Klein-Gordon equation, between neighboring points separated by a space like distance s 2 = (ct) 2 -r 2 < 0 in the ultraviolet region outside the light cone, past and future, violating time-symmetry and local causality.
Keywords: general relativity; cosmology; dark energy; monopole; inflation